Resistant Potato Starch Alters the Cecal Microbiome and Gene Expression in Mice Fed a Western Diet Based on NHANES Data - Smith, Allen D.; Chen, Celine; Cheung, Lumei; Ward, Robert; Hintze, Korry J.; Dawson, Harry D. (Frontiers in Nutrition, 2022)
An abundant literature indicates that the four major types of resistant starch (RS1-4) are fermented in the cecum and colon to produce short-chain fatty acids and can alter the microbiome and host physiology. However, nearly all these studies were conducted in rodents fed a diet that does not approximate what is typically consumed by humans. To address this, mice were fed a Total Western Diet (TWD), based on NHANES data that mimics the macro and micronutrient composition of a typical American diet, for six weeks, and then supplemented with 0, 2, 5, or 10% of the RS2, resistant potato starch (RPS), for an additional three weeks. The cecal microbiome was analyzed by 16S sequencing. The alpha-diversity of the microbiome decreased with increasing consumption of RPS while a beta-diversity plot showed four discreet groupings based on the RPS level in the diet. The relative abundance of various genera was altered by feeding increasing levels of RPS. In particular, the genus Lachnospiraceae NK4A136 group was markedly increased. Cecal, proximal and distal colon tissue mRNA abundance was analyzed by RNASeq. The cecal mRNA abundance principal component analysis showed clear segregation of the four dietary groups whose separation decreased in the proximal and further so in the distal colon. Differential expression of the genes was highest in the cecum but decreased substantially in the proximal colon and further so in the distal colon. Most differentially expressed genes were unique to each tissue with little overlap between tissues. The pattern of gene expression observed suggest that RPS primes the intestine for immune responses to bacteria, parasites and viruses. In summary, consumption of dietary RPS led to significant changes to the microbiome and gene expression in the cecum and to a lesser extent in the proximal and distal colon.